Harmonizing Social Environments And Qur'an Reading Routines: Shaping Moral Character Among Ma Muhyidin Keputih Surabaya Students - Muhamad Syarifuddin Amin; Didit Darmawan (Hikamatzu | Journal of Multidisciplinary, 2024)
Education is the basis for individual development and progress as well as a forum for the formation of a personality with noble character. Morals are among the most important things in Islam and are the essence of understanding and practicing Islamic teachings. Therefore, there are several factors that can influence the formation of morals. This research aims to investigate the influence of the social environment and the routine of reading the Qur’an on the morals of students at MA Muhyidin Keputih Surabaya in classes X, XI and XII with a total of 68 students, taken by census. This research method uses a quantitative approach with regression data analysis techniques. The results of data analysis will be used to identify the extent of the influence of the social environment and the routine of reading the Qur’an on students' morals. The results of this research provide an overview of the influence of the social environment and the routine of reading the Qur’an on the morals of students at MA Muhyidin Keputih Surabaya in classes X, XI and XII. Data analysis using regression shows significant findings